Evolution of the physical characteristics of the French women's rugby players: A 10-year longitudinal analysis by position and team - Imbert, Sébastien; Piscione, Julien; Couderc, Anthony; Joncheray, Hélène; Daussin, Frédéric N. (Frontiers in Sports and Active Living, 2023)
Introduction The study aimed to interpret the evolution of the physical performance of rugby sevens and rugby union French international players from 2009 to 2020. Methods 631 players from the French national teams were divided into three groups: forwards, backs and sevens. The performances evaluated were anthropometric characteristics, strength tests (1 RM bench press and 1 RM pull-up), aerobic capacity (YoYo IR1 test) and speed tests (10 m, 20 m and 50 m). The best performance of each player over a two-year period was kept for the analysis. Fluctuations were observed across the decade. Results The anthropometric characteristics of female rugby sevens players tend to be taller and lighter than rugby union players. In rugby sevens, a moderate increase in maximal aerobic capacity was observed while sprint performances remained similar. Improvements in height and weight were observed over the last 10 years in rugby union players with a difference between the position. A moderate increase in sprinting performances and strength were observed both in backs and forwards. Discussion The overall improvement of strength and conditioning performances and anthropometrical evolution reflects the rugby environment characterized by the arrival of professional contracts and the structuration process of the clubs which allows a better quality of training and easier access to the infrastructures of the very high level.